The impact of name change on the financial performance of savings and credit co-operatives in Kenya - Mathuva, David Mutua; Muthuma, Elizabeth Wangui; Kiweu, Josephat Mboya (Emerald Group Publishing Limited, 2016)
Purpose – This paper aims to investigate the impact of name change, if any on the financial performance of deposit-taking savings and credit co-operatives (SACCOs) in a developing country characterized by a vibrant SACCO sector. Sparse studies exist on the impact of name changes on revenue-cost performance in mutual financial institutionalization. Design/methodology/approach – The study uses a standard event methodology over a six-year period(2008-2013) to investigate the impact of name change on there turn on assets(ROA)and operating profit margin (OPM). The study then uses a panel regression method to study the impact of name change on ROA and OPM for a sample of 212 deposit-taking SACCOs overthe period 2008-2013. Findings – The results, which are robust for a variety of controls, provide evidence in support of a consistent positive association between name change and subsequent financial performance of deposit-takingSACCOsinKenya.Thepositiveimpactofnamechangeseemstobeexperiencedabout fouryearsafterthenamechange.Theresultsrevealmutedinfluenceofregulationonnamechangeand financial performance of SACCOs in Kenya. Research limitations/implications – The study focuses solely on deposit-taking SACCOs in a developing country context over a six-year period only. Extending the time period and including a sample of control SACCOs operating purely back-office service activities would add power to the analyses. Practical implications – Thecurrentstudyillustratesthecontributionofnamechangeonthefinancial performance of SACCOs in a developing country characterized by a vibrant SACCO sector. Overall, the resultsshowthatnamechangeannouncementssignalanimprovementinSACCOs’futureprospects. Originality/value – This study provides empirical evidence on the contribution of name change announcements on the financial performance of SACCOs in a developing country context. The study adds to the sparse literature on the impact of name change on the financial performance of mutual financial institutions that are not listed on the securities exchange.
Keywords: Kenya; Regulator; Financial performance; Name change; Savings and credit co-operative